Genotyping Study of Scedosporium apiospermum Isolates from Patients with Cystic Fibrosis - Defontaine, Alain (American Society for Microbiology, 2002)
Usually a saprophyte, Scedosporium apiospermum often colonizes the respiratory tracts of patients with cystic fibrosis (CF). In order to improve our understanding of the molecular epidemiology of the airway colonization, 129 sequential and multiple isolates collected from January 1998 to March 1999 from nine CF patients monitored in three hospitals in France were typed by random amplification of polymorphic DNA with primers GC70, UBC-701, and UBC-703. Among these primers, UBC-703 was the most discriminating, allowing the differentiation of 14 genotypes. Combining the results obtained with this three-primer set resulted in the differentiation of 16 genotypes. No common genotype was found among the different patients, and no clustering according to geographic origin of the isolates was seen. In addition, five of the patients were colonized by a single genotype. The others usually exhibited a predominant genotype accompanied by one or two others, which were found occasionally and were genetically close to the predominant genotype. Thus, our study demonstrates the persistence of the fungus despite antifungal treatments and therefore reinforces the need for the development of new antifungals that are more efficient against this species.